If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -6 = 18 Reorder the terms: -6 + 6y = 18 Solving -6 + 6y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6y = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 6y = 18 + 6 6y = 18 + 6 Combine like terms: 18 + 6 = 24 6y = 24 Divide each side by '6'. y = 4 Simplifying y = 4
| 8ln(2x)=24 | | 5x+4-3x+1= | | 9(b+4)=108 | | 14+5x=-1 | | 6x+15=5x+7 | | -5-x=-2x+3 | | 5x=27-4x | | 3x^2+6=81 | | X^4-3X^3+11X^2-27X+18=0 | | x^2-25x+27=0 | | x^2+25x+23=0 | | 5x-30+4=7x+14-10 | | 48x+20=6(7x+4)+6x-4 | | x^2+-10x+23=0 | | x^2-10x-23=0 | | x^2+10x-23=0 | | m^2+6m+2=0 | | -5(2x-6)+5=-10x+35 | | 0.10(y-4)+0.12y=0.2y-1.5 | | 7+4(3)=1 | | 8(x+9)+3=75 | | 7+4(-3)=1 | | x^2-4x+49=0 | | 4x^2-5x=3 | | x^2-4x+41=0 | | x^2-4x-41=0 | | x^2+4x-41=0 | | 5(2m+5)=65 | | 2*9=6*x | | 13=5+3b-23 | | 24*32= | | 5X^2-31x+30=0 |